1980
DOI: 10.1111/j.1365-2184.1980.tb00453.x
|View full text |Cite
|
Sign up to set email alerts
|

The Proliferative State of Granulocytic Progenitor Cells in Human Blood and Marrow

Abstract: A double layer agar technique was used to investigate the proliferative state of granulocytic progenitor cells (Colony Forming Units in Culture; CFUc) in human peripheral blood and bone marrow. The sensitivity of the progenitor cells to the S‐phase specific agent, hydroxyurea, was used as an index of the proportion of cells engaged in DNA synthesis. In the presence of low concentrations of colony stimulating factor (CSF) the CFUc were found to be virtually insensitive to the drug. However, when cultured in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The result may be explained in the light of velocity sedimentation profiles and data on DNA synthetic fraction of haemopoietic progenitors. The progenitors in adult blood are homogeneous, small and of low suicidal fraction representing a population of very early cells in the stem cell hierarchy migrating from the bone marrow (21). By contrast cord blood progenitors constitute a more heterogeneous population with respect to the cell volume distribution profile of higher suicidal fraction.…”
Section: Results Of'assaysfor Progenitor Cells In Human Cord Blood Amentioning
confidence: 99%
“…The result may be explained in the light of velocity sedimentation profiles and data on DNA synthetic fraction of haemopoietic progenitors. The progenitors in adult blood are homogeneous, small and of low suicidal fraction representing a population of very early cells in the stem cell hierarchy migrating from the bone marrow (21). By contrast cord blood progenitors constitute a more heterogeneous population with respect to the cell volume distribution profile of higher suicidal fraction.…”
Section: Results Of'assaysfor Progenitor Cells In Human Cord Blood Amentioning
confidence: 99%
“…Standen et al [10] demonstrated that for both human BM and PB MNC as overlayers, colony yield increased linearly with increasing concentrations of feeder cells until a plateau was reached with feeder cell doses of 1 x 109 leukocytes per plate. Therefore, this system provides a sensitive assay for PBL CSA.…”
Section: Discussionmentioning
confidence: 99%